Role of macrophages in the pathogenesis of atherosclerosis and aortocoronary graft disease - Perek, B; Kowalska, K; Kempisty, B; Nowicki, A; Jankowski, M; Nawrocki, M J; Malińska, A (Journal of biological regulators and homeostatic agents, 2018)
Atherosclerosis and disease of graft implanted to bypass occluded coronary or peripheral arteries are similar processes. Patency of implanted grafts is of paramount importance in respect to long-term outcomes. Although few cell types participate in atherosclerotic plaque formation, macrophages play a crucial role. In this article we review the fate of monocytes that infiltrate vessel wall following endothelium damage, and then undergo transformation to macrophages (identified as CD68 positive cells) and eventually lead to severe stenosis of vessel. Opposing biological activity of two subpopulations of macrophages and their impact on plaque instability and its calcification is also presented. At the end of this paper, a possible clinical significance of pre-existing, CD68 positive cell infiltration of vessel wall, applied as aortocoronary grafts, is discussed.
Keywords: Antigens, CD; Graft Rejection; antigeny diferenciační myelomonocytární; CD antigeny; makrofágy; Macrophages; Humans; ateroskleróza; Coronary Artery Bypass; lidé; Atherosclerosis; koronární bypass; rejekce štěpu; Antigens, Differentiation, Myelomonocytic